Pengaruh Pendidikan dan Sanksi Perpajakan Terhadap Motivasi Wajib Pajak Dalam Memenuhi Kewajiban Perpajakan - Freddy, Daulat (Jurnal Ekonomi : Journal of Economic, 2014)
This study was conducted to determine the effect of education on the motivation of taxpayers in meeting tax obligations on STO Jakarta Cakung 1, and the influence of administrative sanctions against the taxpayer motivation in meeting tax obligations on STO Jakarta Cakung 1. Referring to the national tax revenue target in 2013 reached USD 1042.32 trillion or an increase of 24.79% from the previous year, the revenue target accounted for 68.14% of the draft budget to the amount of USD 1529.67 trillion (lens Indonesia 2013).F test is used to test whether the simultaneous effect of independent variables on the dependent variable. The null hypothesis (Ho) to be tested is whether all the parameters in the model is equal to zero, or Ho: β1 = β2 = 0, which means that there is no influence of independent variables on the dependent variable together. While the alternative hypothesis (Ha) is not all parameters simultaneously equal to zero, or Ha: β1 ≠ β ≠ 0, which means that there is the influence of independent variables on the dependent variable together. Significant if the probability of <0.05.T test was used to test individual regression coefficients, with the following terms, Ho: β1 = 0, which means that there is no influence between independent variables with dependent variables. Ha: β1 ≠ 0, which means that there is the influence of the independent variables with the dependent variable individually.Based on the results above SPSS output can be seen the value of the variable for education sig 0.179> 0.05, which means not significant, so education is partially no significant effect on the motivation of the taxpayer in meeting tax obligations or Ho accepted.While the value of the variable administrative penalties 0.000 <0.05, which means that administrative sanctions partially significant effect on the motivation of the taxpayer in meeting tax obligations or Ho is rejected. According to the author of this happens because of the possibility of sanctions is a factor that is avoided by the taxpayer, so the taxpayer to perform its obligations in a timely manner to avoid administrative sanctions that harm taxpayers.Objects used in this study is the STO Jakarta Cakung the study design is causal, the method of data processing, the software SPSS 17 utcomes will be the dissemination of research results at universities in Indonesia and will be published.Keywords: education, administrative sanctions, motivation taxpayer